2000
DOI: 10.1103/physrevb.61.16890
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Stranski-Krastanov growth in 1+1 dimensions with anharmonic interactions: An equilibrium study

Abstract: The formation of coherently strained three-dimensional ͑3D͒ islands on top of the wetting layer in the Stranski-Krastanov mode of growth is considered in a model in 1 ϩ 1 dimensions accounting for the anharmonicity and nonconvexity of the real interatomic forces. It is shown that coherent 3D islands can be expected to form in compressed rather than expanded overlayers beyond a critical lattice misfit. In expanded overlayers the classical Stranski-Krastanov growth is expected to occur because the misfit disloca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 67 publications
1
47
0
1
Order By: Relevance
“…18,19 The mono-bilayer transformation was considered as the first step of the overall 2D-3D transformation and a critical misfit was determined from the misfit dependence of N 12 . The latter was found to increase with decreasing misfit diverging at a critical value ε 12 .…”
Section: A Stability Of Monolayer Islandsmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 The mono-bilayer transformation was considered as the first step of the overall 2D-3D transformation and a critical misfit was determined from the misfit dependence of N 12 . The latter was found to increase with decreasing misfit diverging at a critical value ε 12 .…”
Section: A Stability Of Monolayer Islandsmentioning
confidence: 99%
“…The first step in this transformation should be the rearrangement of monolayer into bilayer islands. 18,19 Khor and Das Sarma found by Monte Carlo simulations that during the rearrangement, the material for the bilayer island comes almost completely from the original monolayer island, the bulk of the material for the three-layer island comes from the original two-layer island, etc. 20 Moison et al reported that the coverage suddenly decreases from about 1.75 ML to 1.2 ML when 3D InAs islands begin to form on GaAs.…”
mentioning
confidence: 99%
“…Moreover, the second layer nucleation in heteroepitaxy differs markedly from that in homoepitaxy. The reason is that the growth of strained 2D island should be accompanied by the relaxation of strain and the decrease of adhesion of atoms at the island perimeter [21][22][23]. It can lead to the increased adatom concentration on the island top.…”
Section: Article In Pressmentioning
confidence: 97%
“…If the misfit is weak, growth will take place layer by layer as in the case of a pure crystal. Experimentally, the 2D-3D instability has quite different features at low misfit [11,12] and it has even been suggested [13,14] that growth is two-dimensional below a critical misfit (about 2%). Therefore, it seems reasonable to believe that the nucleation of new terraces has peculiar features above this critical misfit.…”
Section: Nucleation At Upper Step Edgesmentioning
confidence: 98%